TRADISI AKAD MANDONDON DI MASYARAKAT TAPANULI SELATAN DITINJAU DARI HUKUM ISLAM (STUDI KASUS DI KECAMATAN SIPIROK ) - Nawir Yuslem, Hafsah, M. Kamil Srg (UIN SU, 2018)
Tradition of Mandondon contract is a peopleâs habit in Sipirok sub-district, the south Tapanuli in getting loan (debit) by pawning their rice field to the capital owner, but it will be become as a guarantee and will be controlled by people receiving pawning, and they may cultivate to utilize it, then collects the result of the rice field during debit must be returned by mortgaging with the same amount, so that people who is pawning to be loss.The main problems in this research, (1) how are the essences and the implementation of Mandondon contract in Sipirok sub-district? (2) How are the reviews of Islamic law to tradition of Mandondon contract in Sipirok sub-district?. Then, the general goals achieved in this research are to know the essences and the implementation of Mandondon contract. The particular goals are to know how the reviews of Islamic law to tradition of Mandondon contract. This research is a field research using data analysis method, a qualitative method, using case approach. The data source of this research is people pawning their rice field, the person receiving the pawn, adatâs figure, and MUI chairman.The results of this research shows that practice agreement of Mandondon contract (pawn rice field) if it is seen in qualified term, it is already qualified, but has not fulfilled the principle because in the pawnshop is not yet clear the deadline for repayment of debt which must be done by the mortgage to the receiver of the pledge, then in the implementation that occurs in the Sipirokâs community are not perfect pawnshops or not according to Islamic sharia. In pawn practices, researcher finds that there are elements of usury and utilization of the mortgaged goods.Â